Clinical and Pathological Characteristics of Breast Cancer Patients at Soedarso Hospital Pontianak - Aisha, Ayunda; Pratiwi, Sari Eka; Trianto, Heru Fajar; Suhardiman, Eko Rustianto; Fitrianingrum, Iit (Indonesian Journal of Cancer, 2025)
Background: Breast cancer has been identified as the most commonly diagnosed cancer in Indonesia, contributing to the highest incidence rate in 2020. The clinical characteristics of cancer patients in Indonesia may vary depending on the region, and social and cultural factors can also play a role in these differences. West Kalimantan, a province in Indonesia, is known for its diverse population comprising three significant ethnic groups: Malay, Dayak, and Chinese. This study aims to describe the characteristics of breast cancer patients in West Kalimantan.Method: This study is a descriptive study conducted on patients from 2019 to 2022. The study included 143 breast cancer patients who met the inclusion and exclusion criteria. All medical records were reviewed and analyzed to obtain the variable data; they were age, gender, origin, ethnicity, education, clinical manifestation, stage of breast cancer, tumor size, lymph node metastasis, distant metastases, lymphangioinvasion, histopathology type, and grading.Results: Breast cancer patients for the 2019 to 2022 period totaled 341 patients. Breast cancer has the highest number of cases in 2022, 148 patients. In this study, 143 patients from 2019 to 2022 met the inclusion criteria. Breast cancer was found from age 30 with a peak at the age of 44-50 years, and all patients were women. The highest percentage of patients had completed primary education (28%). Most patients came from Pontianak city (37.1%), with the most ethnic groups being Malays (73.5%). The most common clinical symptom was a painless lump (97.9). Most patients came at stage IIIb (29.4%). Pathological characteristics are tumor size T4 (42%), N1 lymph node metastasis (30.1%), 86.4% of patients had no distant metastasis. A total of 77.6% of patients had negative lymphangioinvasion. Based on histopathology, the type of invasive ductal carcinoma ranks the highest (79%) and had grade 3 breast cancer (47.6%).Conclusion: Breast cancer cases in Soedarso Hospital have increased every year. The majority of breast cancer patients at Soedarso Hospital from 2019 to 2022 were in advanced stages and the type of invasive ductal carcinoma with grade 3.